Managing internal policy risk: Australia, the UK and the US compared. Issue 2 (3rd April 2022) - Howlett, Michael; Leong, Ching; Sahu, Sonam
Abstract: Most studies of risk management examine only exogenous risks – that is, those external to the policy-making process such as the impact of climate change, extreme weather events, natural disasters or financial calamities. But there is also a large second area of concern – "internal risks" or those linked to adverse or malicious behavior on the part of policy makers. This behavior to deceive or "game" the intentions and expectations of government is a part of the policy world which also requires risk management. The paper reviews three archetypal cases of efforts to manage this side of policy risk in the UK, the US and Australia and draws lessons from them about how best to deal with or manage this "darkside" of policy-making.